URGENSI PENDIDIKAN TAUHID PADA ANAK USIA DINI DI ERA GENERASI Z - Nurul Qomaria, Elysa (ILJ: Islamic Learning Journal, 2024)
Tawhid is the main foundation in Islam, so instilling the value of tawhid in early childhood is crucial to ensure a strong religious foundation. Early childhood is likened to a newly growing land, and tawhid education at this stage becomes important so as not to be influenced by teachings that contradict the Islamic creed. In the digital age, where children are easily exposed to various information, monotheism education aims to impress Allah and keep them away from negative influences on faith and morals. The purpose of tawhid education in early childhood in the era of generation Z involves aspects such as instilling love for Allah, thanking Him, knowing the greatness and power of Allah, loving His Apostles, and believing in supernatural things. This discussion uses qualitative literature methods by taking data from relevant literature. The conclusion of this paper emphasizes the importance of tawhid education for early childhood in the era of generation Z, focusing on goals such as sincerely worshiping Allah, understanding the meaning and purpose of worship, and avoiding everything forbidden by Allah, such as shirk.